Commitment to Halal Practices of Indonesian Culinary MSMEs in the Production Chain: The Impact of Halal Literacy and Attitudes - Muhammad Alfarizi; Ngatindriatun (UIN Sulthan Thaha Saifuddin Jambi, 2022)
Indonesia has the potential to become halal tourism during the development of a sizeable Muslim population in the world. Indonesia's diverse cuisine is an essential shot at the halal industry to ensure that the food production process follows halal standards, one of which is through certification. With the role of Culinary MSMEs in implementing the halal production chain, it can meet the spiritual needs of Indonesian Muslims and even the world, as well as being a consideration for cons`1``umers to choose halal cuisine that is guaranteed to be healthy and free of illicit content. This study aims to explore the influence of halal literacy that encourages the knowledge, attitudes, and spirituality of Culinary MSME owners on the commitment of Indonesian Culinary MSMEs to halal practice standards in the food production chain. This study was carried out with a survey of Culinary MSME Owners with Islamic Religious Identity in Indonesia who have gone through a halal assessment process from the MUI or BPJPH of the Ministry of Religion of the Republic of Indonesia, and the data results were analyzed using Structural Equation Modeling (SEM). The results showed that halal literacy is a driving factor for Islamic knowledge, attitudes, and spirituality in the commitment of Indonesian Culinary MSME owners to standard halal practices in the production chain. This study forms three implications for Indonesian Culinary MSME owners, the Government, and Academics.